A new DAWN: Improving the psychosocial management of diabetes - Holt, Richard I. G. (Medknow Publications & Media Pvt Ltd, 2013)
AIMS: The second Diabetes Attitudes, Wishes and Needs (DAWN-2) study assessed psychosocial issues and health-care provision of people with diabetes, their family members and health-care professionals. MATERIALS AND METHODS: Participants completed an online, telephone or in-person survey designed to assess health-related quality-of-life, self-management, attitudes/beliefs, social support and priorities for improving diabetes care as well as health-care provision and the impact of diabetes on family life. RESULTS: A total of 8596 adults with diabetes, 2057 family members of people with diabetes and 4785 health-care professionals across 17 countries completed the survey. There were significant between country differences, but no one country's outcomes were consistently better or worse than others. A high proportion of people with diabetes reported likely depression (13.8%) and poor quality-of-life (12.2%). Diabetes had a negative impact on many aspects of life, including relationships with family/friends and physical health. A third of family members did not know how to help the person with diabetes, but wanted to be more involved in their care. Many health-care professionals indicated that major improvements were needed across a range of areas including health-care organization, resources for diabetes prevention, earlier diagnosis and treatment and psychological support. CONCLUSIONS: DAWN-2 is a multinational, multidisciplinary systematic study that compared unmet needs of people with diabetes and those who care for them in 17 countries across four continents. Its findings should facilitate innovative efforts to improve self-management and psychosocial support in diabetes, with the aim of reducing the burden of disease. The implications for India are discussed.